Political Connection and Cost of Capital Indonesian Case Study - Abiprayu, Kris Brantas (Universitas Negeri Semarang, 2021)
This research aims at examining the impact of political connection on financing facilitation by measuring cost of capital imposed to non-finance companies in Indonesia from 2009-2017. During the period, there is a change in the Indonesian government which is initially led by President Yudhoyono (2009-2014) from the Democratic Party and then by President Joko Widodo (2014-now) from the Indonesian Democratic Party of Struggle. Opposing one another, both parties share different political views. Therefore, it is interesting to find out how governmental change influence cost of capital. The research sample is financial statements of non-finance companies.